Dampak Pemanfaatan Mobile Banking dan Kebijakan KUR pada Pertumbuhan UMKM di Kecamatan Rungkut - Johanes Putra Mayninedo; Muhammad Yasin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the influence of Information Technology and People's Business Credit Policy on MSME Growth in Rungkut District, Surabaya. The study uses a Quantitative Descriptive approach. The population of the study was MSME business actors in Rungkut District, Surabaya. The method of determining the number of samples through the Purposive Sampling method with the criteria a) Having an MSME business in Rungkut District, Surabaya and b) Utilizing banking facilities in the form of information technology or people's business credit, so that the number of samples was 60 MSME business actors in Rungkut District, Surabaya. The data collection technique was through distributing questionnaires and analyzed through SPSS analysis. The results of the study prove that Information Technology and People's Business Credit Policy have a significant effect on MSME Growth in Rungkut District, Surabaya, partially and simultaneously